Effect of circular openings on web crippling of unlipped channel sections under end-two-flange load case - Elilarasi, K.; Kasthuri, S.; Janarthanan, B. (The Hong Kong Institute of Steel Construction, 2020)
Cold-formed steel unlipped channels with web openings increasingly employed as bearers and joists in the floor systems to embed the building services to maintain adequate clear storey-height and aesthetic appearance. The use of thin-unlipped channels is limited in the past due to flange buckling and mostly web crippling behaviour of lipped channels with web openings was investigated. However, with the thickness increment, the flange buckling of unlipped channels is limited, and these sections are used widely in construction. The major drawback with these cold-formed steel profiles is web crippling, localized failure due to higher web slenderness ratio. Web openings reduce the carrying web area of the sections, hence makes the unlipped channels more vulnerable to web crippling. Currently, unlipped channels with web openings are increasingly employed, although no proper guidelines are available to determine the capacity reductions due to the introduction of web openings. The main cold-formed steel specifications such as North American Specification (AISI S100) and Australian/ New Zealand standard (AS/NZS 4600) employ the unified design equation with different coefficients for all four load cases while Eurocode 3 Part 1-3 (ECS) employs different equations for each load case. In these specifications, design guidelines are available only for offset web openings for unlipped channels under one-flange load cases. This study investigates the effects of circular centred beneath and offset web openings on the capacity reduction of unfastened support unlipped channels subject to web crippling under end two flange load cases. The suitable reduction factor equations have been proposed for circular web openings of unlipped channels located directly underneath and away for the bearing plate using the outcome form the numerical study.
Keywords: Web crippling; Cold-formed steel; Cold-formed steel; Finite element analysis; End-Two-Flange(ETF); Web openings